Anqing Huangmei Opera, Anhui Province, China: Re-Invention of Tradition in the Process of National Intangible Cultural Revitalization - Jin, Qian; Xiaofang, Tu (Journal of Ecohumanism, 2025)
The Anqing Huangmei Opera originated in Huangmei County, Hubei Province, dating back to the Qianlong period of the Qing Dynasty (1764-1786), approximately 230-260 years ago. In 2006, Anqing Huangmei Opera was rightfully included in the first batch of the National Intangible Cultural Heritage representative projects. This study employs a qualitative research methodology and utilizes the concept of "The Re-Invention of Tradition" as a framework to uncover the essential cultural practices of Anqing Huangmei Opera in the context of National Intangible Cultural Revitalization. The research focuses on three main objectives: (1) Examining the historical development of Huangmei Opera in Anqing; (2) Analyzing the foundations of innovation within Anqing Huangmei Opera; (3) Investigating the mechanisms of "Re-Invention of Tradition" as it pertains to Anqing Huangmei Opera in the process of National Intangible Cultural Revitalization. This study employs rigorous field investigations and in-depth interviews to gather relevant data, applying the "Re-Invention of Tradition" concept for comprehensive text and case analysis. The findings decisively illustrate that Anqing Huangmei Opera has consistently adapted and re-innovated its traditions to meet the demands of contemporary socio-political, economic, and cultural landscapes. This approach is not merely about restoring traditions; instead, it actively cultivates a strong sense of cultural identity and social cohesion that underpins the development of present-day society through the strategic re-invention of its traditions.